Function and role of system enzyme therapy in rehabilitation of patients with acute and chronic cerebral ischemia - V. V. Yefremov; Yu. I. Sternin; V. S. Sergienko (Бюллетень сибирской медицины)
Main effects of system enzyme therapy (SET) are antiinflammatory, fibrinolythic and immunomodulating. Combination of these effects proved to be important in the treatment of 30 patients with stroke and 30 patients with ischemic cerebrovascular diseas. The use of polyfermental preparation flogenzyme in complex therapy allowed to normalize the state of thrombocytic hemostasis and to improve the indexes of plasmatic hemostasis and rheology of blood, serum concentration of proinflamatory cytokines (TNF-α, IL-1β, IL-4) to a considerably greater degree than in control group (39 patients) and impaired velocity and reactivity parameters (33 control). Thus, SET medications are necessary and very important pathogenetically in the complex therapy of patients with acute and chronic cerebral ischemia.